Training Program for The Making of Educative Game Tools for Traveling Traffic Games for - Fauzi Khair; Dhendy I.W (Bina Nusantara University, 2021)
This community services activity in the field of science aims to improve the ability of kindergarten teachers and PAUD tutors in making educational Game Tools for traffic signs for learning knowledge about traffic discipline on the highway so that learning activities are fun and useful. This activity is divided into several training schemes with the aim of (a) Making educational traffic aids in kindergartens and PAUD, (b) Designing and implementing quality learning and (c) evaluating the learning of basic knowledge about traffic discipline oriented to safety and security . Training in the form of workshops and assistance in making learning systems and teaching prototypes. The output of PKM is the compilation of training modules and scientific articles on integration in the field of engineering and basic education studies which become a reference for the development of learning systems in kindergarten and early childhood education